Accounting Recording System Design at Harapan Jaya Workshop - Ivone Ivone; Tania Aulia Warni (Universitas Internasional Batam, 2023)
Harapan Jaya Workshop is a business engaged in the work and service of lathe welding on heavy equipment, car equipment, PT / factory goods and shipping. Harapan Jaya has been running for twelve years but still has a fairly traditional accounting system. Harapan Jaya Workshops still use a simple recording system that uses a book to record business transactions. Recording using only this book causes ineffectiveness in recording transactions. Things that often occur include reporting errors such as payment recapitulation, errors occur in data recording due to manual data recording. From the problems above aims to assist the owner in running and managing finances. As well as helping the Workshop to design an accounting recording system to make financial reports that are accurate, neat and correct. Interview is a method used to collect the necessary data. The system used in this project is Microsoft Access. The project was carried out for 5 months from august to december. The budget used in this project is 5 million, including costs for transportation, food, internet and others. This system will provide recording forms for cash disbursement transactions, purchases, sales, and inventory recording. The result of this research is to produce complete and accurate financial reports consisting of profit and loss reports, purchases, sales, remaining inventory, and trial balance.